Effects of Flaxseed (Linum usitatissimum) Extract on the Osteoblast Differentiation Potential of Stem Cells Derived from Human Exfoliated Deciduous Teeth - Nordin, Nur Sazwi; Mokhtar, Khairani Idah; Mustafa, Basma Ezzat; Lestari, Widya; Ichwan, Solachuddin JA Ichwan Jauhari Ichwan; Darnis, Deny Susanti; Kannan, Thirumulu Ponnuraj; Ahmad, Azlina (Makara Journal of Health Research, 2021)
Background: Flaxseed promotes bone health and possibly induces bone regeneration. However, the capacity of flaxseed to induce the differentiation of stem cells into osteoblasts remains unreported. Accordingly, this study aimed to determine the effects of flaxseed extract on the osteoblast differentiation potential of stem cells derived from human exfoliated deciduous teeth (SHED). Methods: SHED cultured in osteoblast induction media (OIM) were treated with 4 mg/mL flaxseed extract. RNA was collected and extracted with Total RNA Mini Kit (Geneaid) from cells cultured at days 1, 3, 7, 14, and 21 and subjected to reverse-transcriptase PCR for osteoblast markers (OSX, OCN, and DMP1). Alkaline phosphatase (ALP) activity was determined by ALP assay, and Alizarin Red-S staining was performed to evaluate calcium deposition in SHED. Results: All osteoblast markers were expressed in all samples analyzed. OSX expression was reduced in the SHED treated with flaxseed extract. In addition, the SHED treated with flaxseed extract had lower ALP activity than the control (p < 0.05). Calcium deposition was positive in the SHED cultured in OIM only. Conclusions: Flaxseed can reduce the expression of osteoblast markers, ALP activity, and calcium deposition in SHED. Thus, flaxseed potentially inhibits the osteoblast differentiation of SHED.